2020
DOI: 10.3389/fneur.2020.00849
|View full text |Cite|
|
Sign up to set email alerts
|

Gut–Brain Axis: Potential Factors Involved in the Pathogenesis of Parkinson's Disease

Abstract: Increasing evidence suggests an association between gastrointestinal (GI) disorders and susceptibility and progress of Parkinson's disease (PD). Gut-brain axis has been proposed to play important roles in the pathogenesis of PD, though the exact pathophysiologic mechanism has yet to be elucidated. Here, we discuss the common factors involved in both PD and GI disorders, including genes, altered gut microbiota, diet, environmental toxins, and altered mucosal immunity. Large-scale prospective clinical studies ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…New attention to the importance and function of the appendix proved that it has a significant role in the immune system of the gut, the microbiome, and the possibility of being a port of transfer of misfolded branched Asyn protein by a prion-like process through the vagus nerve to the brainstem then to be disseminated to the brain reaching different areas explaining the different clinical and pathological findings [8,10,13]. A significant laboratory and animal study supported this gut-brain axis hypothesis [12]. Truncal vagotomy may be associated with a lower incidence of PD [14].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…New attention to the importance and function of the appendix proved that it has a significant role in the immune system of the gut, the microbiome, and the possibility of being a port of transfer of misfolded branched Asyn protein by a prion-like process through the vagus nerve to the brainstem then to be disseminated to the brain reaching different areas explaining the different clinical and pathological findings [8,10,13]. A significant laboratory and animal study supported this gut-brain axis hypothesis [12]. Truncal vagotomy may be associated with a lower incidence of PD [14].…”
Section: Introductionmentioning
confidence: 91%
“…Non-motor manifestations of PD like anosmia, constipation, depression, dementia, sleep disturbances, and other autonomic dysfunction suggest that PD is not restricted to SNpc, but rather a multisystem disease involving other parts of the central and peripheral nervous system [9]. The discovery of Asyn in the mucosa of the gastrointestinal tract [10,11], particularly in the vermiform appendix, proposes a possible link between the gut and the brain: the gut-brain axis [12]. New attention to the importance and function of the appendix proved that it has a significant role in the immune system of the gut, the microbiome, and the possibility of being a port of transfer of misfolded branched Asyn protein by a prion-like process through the vagus nerve to the brainstem then to be disseminated to the brain reaching different areas explaining the different clinical and pathological findings [8,10,13].…”
Section: Introductionmentioning
confidence: 99%
“…Misfolded α-syn aggregates, otherwise known as Lewy body deposits, contribute to the degeneration of dopaminergic neurons within the substantia nigra and other related circuitry (Spillantini et al, 1997(Spillantini et al, , 1998Trojanowski and Lee, 1998), and ultimately the onset of several cardinal motor and non-motor features of PD including dementia, gastrointestinal (GI) dysfunction, tremor, postural instability, bradykinesia, and rigidity (Váradi, 2020). Although most commonly located in the brain, α-syn aggregates have also been found in peripheral locations, such as the enteric nervous system (ENS), lending support to the idea of a "gutbrain axis, " a bidirectional communication pathway between the central and enteric nervous systems and the GI system (Chao et al, 2020; Figure 1).…”
Section: Introductionmentioning
confidence: 95%
“…These mutations may trigger misfolding and abnormal aggregation . Additionally, α-synuclein amyloid aggregates were discovered in sites other than the brain like the enteric nervous system . Clinicopathological evidence has shown that abnormal aggregation of α-synuclein has been observed in gastrointestinal neurons and gastrointestinal tissue of PD sufferers. , Animal experiments have shown that mice’s duodenum wall is injected with preformed α-synuclein fibrils, resulting in gastrointestinal defects and pathological changes in the intestinal nervous system.…”
Section: Misfolded Proteins Are Like the Black Sheep Are They Infecti...mentioning
confidence: 99%